2021
DOI: 10.1017/s0022149x21000122
|View full text |Cite
|
Sign up to set email alerts
|

Avian schistosome species in Danish freshwater lakes: relation to biotic and abiotic factors

Abstract: Due to the increased prevalence of human infections with bird schistosome larvae (cercarial dermatitis) associated with bathing in Danish lakes, a nationwide survey of infected intermediate host snails was conducted in 2018–2020. Pulmonate snails (10,225 specimens) were collected from 39 freshwater lakes (in the four major geographic regions in Denmark) and subjected to shedding. Released schistosome cercariae were isolated and identified by polymerase chain reaction and sequencing whereby Trichobilharzia rege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Furthermore, this mollusk species acts as an intermediate host for zoonotic avian schistosomes in North America [ 2 , 11 ] and recently in Europe [ 25 ]. Considering the reduced prevalence rates associated with these parasites (e.g., Horák & Kolářová [ 6 ]; Marszewska et al [ 8 ]; Brant & Loker [ 11 ]; Al-Jubury et al [ 36 ]), the absence of parasitism by schistosomes in the remaining snail species studied here, such as P. acuta , could be related to the small sample size per area, per snail species (in some cases), or it could even be considered an expected result. However, P. acuta yielded negative results despite its large sample size when compared with C. dombeyana , as there were 1390 versus 714 snails, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this mollusk species acts as an intermediate host for zoonotic avian schistosomes in North America [ 2 , 11 ] and recently in Europe [ 25 ]. Considering the reduced prevalence rates associated with these parasites (e.g., Horák & Kolářová [ 6 ]; Marszewska et al [ 8 ]; Brant & Loker [ 11 ]; Al-Jubury et al [ 36 ]), the absence of parasitism by schistosomes in the remaining snail species studied here, such as P. acuta , could be related to the small sample size per area, per snail species (in some cases), or it could even be considered an expected result. However, P. acuta yielded negative results despite its large sample size when compared with C. dombeyana , as there were 1390 versus 714 snails, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For trematodes, the increase in water temperature would accelerate the development rates inside snail hosts, causing the emergence/re-emergence of these parasites [ 40 ]. Consequently, for zoonotic schistosomes, this would translate into an exacerbated transmission to humans, causing outbreaks of CD [ 3 , 36 ]. The current climatic scenario is of concern, highlighting the need for additional research on the early identification of potential zoonotic schistosomes in understudied areas, such as the Neotropics.…”
Section: Discussionmentioning
confidence: 99%
“…The first Danish cases of human cercarial dermatitis were recorded in Hjørring, Jutland in the 1950s [ 10 ] although Wesenberg-Lund (1934) [ 11 ] much earlier mentioned the occurrence of avian schistosomes in Danish freshwater bodies. Recently, several studies have reported occurrence of bird schistosomes ( T. franki, T. regenti, T. szidati, and T. anseri ) in several lakes in Denmark [ 6 , 12 ]. The summer of 2019 was unusual warm, and recreational places were crowded with bathers and athletes seeking freshwater.…”
Section: Discussionmentioning
confidence: 99%
“…In general, it seems logical to think that increased temperatures will speed up schistosome development times and increase cercariae production in snails and favor transmission [ 16 , 169 , 170 ]. Warming temperatures in places such as Denmark may already be responsible for increases in dermatitis noted there [ 171 ]. These effects might be offset by higher rates of mortality for both cercariae released from infected snails [ 171 ] and of infected snails [ 172 ].…”
Section: Outlook and Priorities For Future Workmentioning
confidence: 99%
“…Warming temperatures in places such as Denmark may already be responsible for increases in dermatitis noted there [ 171 ]. These effects might be offset by higher rates of mortality for both cercariae released from infected snails [ 171 ] and of infected snails [ 172 ]. As noted by Żbikowska and Marszewska [ 119 ], infected snails may seek lower temperatures as a way to reduce their mortality rates following infection, also lowering their rate of cercariae production in the process.…”
Section: Outlook and Priorities For Future Workmentioning
confidence: 99%